Academic entrepreneurship and the research productivity in Poland. Issue 4 (21st April 2021) - Bojko, Marta M.; Knapińska, A.; Tomczyńska, Aldona
ABSTRACT: Is it possible to reconcile academic entrepreneurship with the internationalisation of scientists' productivity? We provide an answer to this question through the statistical analysis of a representative survey of 811 scientists in Poland. Based on Robert K. Merton's distinction between two types of scholars: local (oriented towards the national science system) and cosmopolitan (aiming at international achievements), we found that research productivity positively influences academic entrepreneurship, but that scientists who are productive locally engage in academic entrepreneurship more often than the cosmopolitan ones. This suggests that the internationalisation of one's scientific activity, at least in countries transitioning from a local to a cosmopolitan mode of research, is an absorbing endeavour that only the most productive researchers can reconcile with academic entrepreneurship. Such countries should balance their policies regarding the career development of their scientists also to include the promotion of science-business cooperation and not just the internationalisation of research.